1986
DOI: 10.1128/jb.168.2.799-804.1986
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunochemical properties of the cell surface of Renibacterium salmoninarum

Abstract: The biochemical composition of the cell envelope of Renibacterium salmoninarum was investigated in a total of 13 strains isolated from different salmonid fish species at various geographicil locations of the United States, Canada, and Europe. A marked similarity with the type strain R. salmoninarum ATCC 33209 was found both in the peptidoglycan and the cell wall polysaccharide. The primary structure of the peptidoglycan was found to be consistent with lysine in the third position of the peptide subunit, a glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…E-mail: rstevens@micro.uoguelph.ca for electron microscopy. They suggested it was composed of the polysaccharide described by Fiedler & Draxl (1986), but did not confirm the result chemically. Firnbrae were observed on the surface of R. salmoninarum (Dubrueil et al 1990b) and, on the basis of immunogold staining with a polyclonal antiserum, it was suggested that these structures were composed of p57.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…E-mail: rstevens@micro.uoguelph.ca for electron microscopy. They suggested it was composed of the polysaccharide described by Fiedler & Draxl (1986), but did not confirm the result chemically. Firnbrae were observed on the surface of R. salmoninarum (Dubrueil et al 1990b) and, on the basis of immunogold staining with a polyclonal antiserum, it was suggested that these structures were composed of p57.…”
Section: Introductionmentioning
confidence: 79%
“…The capsule is lacking in the cryosections of MT 239, as would be expected if the p57 material is being released into the culture medium. If p57 does form such a capsule, this would explain the description by Fiedler & Draxl(1986) of a surface-associated carbohydrate surrounding R. salmoninarum, providing congruity between 2 ideas about the composition of the surface layer on renibacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…4). Finally, strains of R. salmoninarum are highly homogeneous with respect to the overall genomic structure, biochemical properties, and surface antigens (24,27,53,68).…”
Section: Discussionmentioning
confidence: 99%
“…The widely used algorithms that transform pairwise 16S rDNA similarity values into dissimilarity values, including the compensation for multiple substitutions that may occur at the same site Schleifer & Kandler (1972), Kalakoutskii (1989), Collins et al (1989), Martin et al (1997), Prauser et al (1997), Schumann et al (1997) and Busse & Schumann (1999). Data for the Micrococcaceae from Schleifer & Kandler (1972), Collins (1982), Embley et al (1983), Jones & Collins (1986), Gerencser & Bowden (1986), Stackebrandt et al (1983), Schleifer (1986), Fiedler & Draxl (1986), Stackebrandt et al (1995) and Gvozdiak et al (1998) Intrasporangiaceae Intrasporangium…”
mentioning
confidence: 99%